Method for preparing heteropolyacid from scheelite in short process and application of heteropolyacid to flow battery

Through the water-impregnation and acid-decomposition reaction of syringe tungsten and sodium silicate, the Keggin configuration silicon-tungsten heteropolyacid is self-assembled, and through multi-step purification, it realizes efficient and low-cost heteropolyacid preparation, solving the problems of low resource utilization efficiency of syringe tungsten and complex preparation of liquid flow battery electrolyte, and promoting the development of high-energy density liquid flow batteries.

CN119911917AActive Publication Date: 2025-05-02CENT SOUTH UNIV

Patent Information

Application Number
CN202510120192.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-05-02
Estimated Expiration
2045-01-25

AI Technical Summary

Technical Problem

In the prior art, the utilization efficiency of sedraelite resources is low, and the preparation process of the electrolyte of the heteropoly acid flow battery is complex and costly, which seriously restricts the development of flow battery.

Method used

By reacting sedratinite with sodium silicate under water immersion and acidolysis conditions, self-assemble to form the Keggin configuration silicon-tungsten heteropoly acid, and the preparation of high-performance heteropoly acid is achieved through solid-liquid separation, precipitation, redissolution, acidification-extraction and recrystallization.

Benefits of technology

It has achieved clean and efficient utilization of sedraelite, significantly reduced the production cycle and cost of liquid flow battery electrolyte, reduced the pressure of environmental pollution, and provided a new technical approach for the development of high-energy-density liquid flow battery system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911917A_ABST
    Figure CN119911917A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing heteropolyacid from scheelite in a short process and application of the heteropolyacid to a flow battery, and the preparation method comprises the following steps: S1, carrying out water leaching and acidolysis on scheelite and sodium silicate according to a molar ratio of W to Si of (1-3): 1, and then carrying out solid-liquid separation to remove insoluble substances; s2, adding a precipitant into the leachate to enable the silicotungstic heteropoly acid to form silicotungstate precipitation, so as to realize salting-out-precipitation purification of the Keggin-configuration silicotungstic heteropoly acid; and S3, redissolving the silicotungstate precipitate obtained in the step S2, acidifying, extracting, recrystallizing and purifying to obtain the Keggin configuration silicotungstic heteropoly acid with battery grade purity. The invention innovatively provides a method for in-situ decomposition of scheelite and direct short-process preparation of the heteropolyacid electrolyte for the flow battery, so that clean and efficient utilization of tungsten resources is realized, and a new technical approach is provided for short-process preparation of the heteropolyacid flow battery electrolyte; and the production cycle and the cost of the electrolyte of the flow battery are obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the application of scheelite, and in particular to a method for preparing heteropoly acid from scheelite in a short process and the application of the method in a liquid flow battery. Background Art

[0002] With the growing global demand for the widespread use of renewable clean energy and long-term energy storage, flow batteries, as a safe, efficient and long-life energy storage technology, have gradually attracted widespread attention. At present, the widely studied flow batteries mainly include: all-vanadium flow batteries, all-iron flow batteries, iron-chromium flow batteries, zinc-bromine flow batteries, zinc-manganese flow batteries, heteropolyacid flow batteries, etc.

[0003] The electrolyte is one of the key components of flow batteries, and its performance directly affects the capacity, energy density, stability, and cycle life of the battery. The preparation of high-performance electrolytes often relies on complex chemical synthesis processes, which are long and costly, and may produce harmful byproducts during the production process, posing a threat to the environment.

[0004] More importantly, all-vanadium liquid flow batteries, iron-chromium liquid flow batteries, and zinc-bromine liquid flow batteries, which have gradually been commercialized, still face significant challenges such as low battery energy density and limited capacity because they only store charge through single-electron / two-electron redox.

[0005] On the one hand, heteropolyacids have unique advantages as charge carriers in the field of electrochemical energy storage. Their multi-electron redox properties, strong stability, high solubility, adjustable redox potential, and customizable structure make them show great potential in enhancing the energy density of flow batteries. However, traditional methods use highly pure chemical reagents, and the preparation of heteropolyacids faces obvious problems such as long processes, high costs, and low efficiency, which seriously restricts the development of heteropolyacid flow batteries.

[0006] On the other hand, tungsten ore, as a non-renewable strategic scarce resource, plays an important role in the fields of military industry, electronics, aerospace, chemical industry, biomedicine, etc. However, the complex process of exploration, mining, beneficiation, smelting, processing, etc. of scheelite to make tungsten chemical products such as tungstic acid, sodium tungstate, calcium tungstate, ammonium metatungstate (AMT), ammonium paratungstate (APT) for the next stage of use not only has a long cycle and high energy consumption, but also has high production costs and puts great pressure on the environment. How to shorten the processing flow, reduce production costs, and achieve efficient utilization of tungsten resources while ensuring no pollution to the environment is an important challenge facing the current field of clean and efficient utilization of tungsten metallurgy.

[0007] Therefore, it is urgent to establish a systematic technical process connection for the efficient and clean utilization of scheelite and the short-process and low-cost preparation of heteropolyacid flow battery electrolytes, so as to provide new solutions for the development of long-term energy storage technology, especially high-energy density flow battery systems. Summary of the invention

[0008] In view of the problem of low utilization efficiency of scheelite resources mentioned above, the present invention provides a method for preparing heteropoly acid from scheelite in a short process and its application in flow battery, organically combining tungsten ore hydrometallurgy with the preparation process of flow battery electrolyte, and innovatively providing a method for in-situ decomposition of scheelite and direct short-process preparation of high-performance heteropoly acid for flow battery electrolyte.

[0009] In order to achieve the above object, the present invention provides a method for preparing heteropoly acid from scheelite in a short process, which comprises the following steps: S1. Scheelite and sodium silicate are soaked in water and acid-lyzed at a molar ratio of W to Si (1-3):1, so that the decomposed WO 4 2- With SiO 3 2- Under acidic conditions, it self-assembles into a Keggin-structured silicotungstic acid, whose molecular formula is H 3 [SiW 12 O 40 ]·xH 2 O, and then solid-liquid separation is performed, wherein x represents the amount of crystal water, which is not a fixed value and is related to the type of cation, the synthesis and purification method, the storage time, etc., and is 9 to 17 in the present invention; S2. Adding a precipitant to the leaching solution to make the silicotungstic heteropoly acid form silicotungstate precipitate, so as to achieve the preliminary purification of the Keggin configuration silicotungstic heteropoly acid; the precipitant can form a salt compound with a lower compound solubility with the silicotungstic heteropoly acid to form silicotungstate precipitate; S3, re-dissolving the silicotungstate precipitate obtained in step S2, and performing acidification, extraction, and recrystallization to obtain silicotungstic heteropoly acid with battery-grade purity.

[0010] Preferably, in step S1, the scheelite has been previously treated for impurity removal and purification, wherein the tungsten element grade is greater than 40%, and the particle size is controlled at 0.038-0.074 mm.

[0011] Specifically, in step S1, the water immersion conditions are: 75-90°C, solid-liquid ratio of 1g: (1-2mL), 1.0-2.0h.

[0012] Specifically, in step S1, the acid hydrolysis conditions are: pH value 4.5-5.5, temperature 90-100°C, solid-liquid ratio 1:(3-10), mass of scheelite and sodium silicate: volume of water and acid = 1:(3-10), time 2.5-5.0 h.

[0013] Specifically, in step S1, the molecular formula of the silicotungstic heteropoly acid having Keggin configuration is.

[0014] Preferably, in step S2, the precipitant is one or more of ammonium chloride, potassium chloride, sodium chloride, and tetrabutylammonium chloride.

[0015] Preferably, in step S3, the redissolution temperature is 40-50°C.

[0016] Preferably, in step S3, the acidification is carried out using hydrochloric acid, the extraction is carried out using ether, and the ratio of the weight of silicotungstic heteropoly acid, the volume of water, the volume of hydrochloric acid, and the volume of ether is 2:5:3:2.

[0017] Further preferably, in step S3, the acidification-extraction times are 2 to 3 times, and the recrystallization times are more than 2 times.

[0018] The second aspect of the present invention provides the use of the heteropolyacid prepared by the above method in preparing a liquid flow battery electrolyte.

[0019] Through the above technical solution, the present invention achieves the following beneficial effects: 1. The present invention innovatively provides a method for in-situ decomposition of scheelite and direct short-process preparation of high-performance Keggin-configured silicotungstic heteropoly acid for liquid flow battery electrolyte, which not only realizes the clean and efficient utilization of tungsten resources, but also provides a new technical approach for the short-process preparation of heteropoly acid liquid flow battery electrolyte. By directly obtaining silicotungstic heteropoly acid electrolyte materials from tungsten ore raw materials, the production cycle and cost of liquid flow battery electrolytes are significantly reduced, and the pressure of environmental pollution is significantly reduced, providing a new solution for the storage of renewable energy such as solar energy and wind energy.

[0020] 2. The Keggin-structured tungstic silicon heteropoly acid prepared by the present invention is used as the negative electrode electrolyte of the flow battery, which can achieve a maximum of 3 [SiW 12 O 40 ]·xH 2 O) can achieve 100% SOC (SOC is the abbreviation of State of the charge), which is conducive to further building a high energy density liquid flow battery system. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 11 is a short process flow chart for preparing heteropolyacids according to an embodiment of the present invention; Figure 2 : is a three-layer liquid distribution diagram of the Keggin silicotungstic heteropoly acid extraction process in an embodiment of the present invention; Figure 3 The Keggin silicotungstic acid & ether extraction mixture in the embodiment of the present invention; Figure 4 It is the Keggin silicotungstic heteropoly acid product in the embodiment of the present invention; Figure 5 is the cyclic voltammetry curve of Keggin silicotungstic heteropoly acid in the embodiment of the present invention; Figure 6 It is a coulombic efficiency and capacity diagram of the charge and discharge cycle process of the 0.2 mol / L Keggin silicotungstic heteropoly acid 1~12e flow battery in an embodiment of the present invention. DETAILED DESCRIPTION

[0022] The specific implementation of the present invention is described in detail below in conjunction with the examples. It should be understood that the specific implementation described herein is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0023] In the following examples, scheelite is natural high-purity scheelite (CaWO 4(s) Composition greater than 99%, WO 3 When the content is greater than 79%, it is crushed and ground, and the particle size is controlled at 0.038~0.074 mm.

[0024] Example 1 like Figure 1 As shown, the short process preparation method of heteropoly acid is as follows: (1) Decomposition of scheelite and synthesis of silicotungstic heteropoly acid Weigh 50 g of calcium tungstate (CaWO 4(s) ) as the main component of scheelite powder and 20.88 g sodium silicate (Na 2 SiO 3 ) were added as precursors to the bottom of a three-necked flask, and an appropriate amount of 80 ℃ deionized water was added for soaking for 1.5 h; then, 4.0 mol / L hydrochloric acid was slowly added dropwise under strong stirring conditions, and the reaction was carried out for 4.0 h at a pH of 4.5-5.5, a temperature of 90 ℃, and a solid-liquid ratio of 3. After the reaction, the reaction mixture was filtered to separate the solid and the liquid, and the solution was retained. Keggin-structured silicotungstic heteropoly acid with a fixed ratio was obtained in the solution.

[0025] (2) Purification of battery-grade tungsten-silicon heteropoly acid electrolyte Add salt compounds with low solubility that can form compounds with silicotungstic heteropolyacids such as ammonium chloride, potassium chloride, sodium chloride, and tetrabutylammonium chloride to the filtered solution to form silicotungstate precipitates to achieve preliminary impurity removal of Keggin-configured silicotungstic heteropolyacids. The silicotungstate precipitate is dissolved in deionized water at 45 °C, and concentrated hydrochloric acid and ether are added and shaken (such as Figure 2 As shown in the figure, the Keggin silicotungstic acid extraction process presents a three-layer liquid distribution, which is ether layer-impurity mixed leachate layer-silicotungstic acid & ether extract layer from top to bottom). The lowest layer of the mixed solution is transferred to another separatory funnel ( Figure 3 The Keggin silicotungstic acid & ether extraction mixture) is then purified by 2 times of hydrochloric acid acidification and ether extraction. The oily solution at the bottom of the separatory funnel is evaporated by a rotary evaporator and dried to obtain silicotungstic heteropoly acid (such as Figure 4 As shown). To ensure the purity, the obtained tungsten silicon heteropoly acid is recrystallized three times to obtain battery-grade purity tungsten silicon heteropoly acid (wherein the content of tungsten silicon heteropoly acid is ≥99.5%, the content of impurities Na, K, Ca, Fe, Zn, and Cl are not higher than 0.003%, and the leaching rate of scheelite is 99.54%). In the process of re-dissolution of tungsten silicon salt precipitation and acidification-ether extraction, the weight of tungsten silicon heteropoly acid: water volume: hydrochloric acid volume: ether volume usage ratio basically meets 2:5:3:2.

[0026] (3) Silicon tungsten heteropoly acid-based flow battery test The purified Keggin-structured tungstic silicon heteropoly acid was used as an active material to prepare a negative electrode electrolyte, wherein the negative electrode electrolyte was 0.2 mol / L tungstic silicon heteropoly acid + 2.5 mol / L sulfuric acid, and the positive electrode electrolyte was 1.5 mol / L vanadyl sulfate (VOSO 4 )+3.0 mol / L sulfuric acid, proton exchange membrane Nafion 117, positive and negative electrode materials graphite felt, test fixtures, etc. were assembled into an asymmetric aqueous flow battery and its battery performance was tested. The test method is: 100 mA / cm 2 The charging and discharging were performed at constant current, the charging cut-off condition was the capacity cut-off (i.e. the capacity corresponding to the charged state of the silicon tungstic heteropoly acid), and the discharging cut-off condition was 0 V.

[0027] Test results such as Figure 5~Figure 6 As shown: from Figure 5 It can be seen that the Keggin-configured silicotungstic acid prepared by the short process of scheelite has three pairs of reversible redox peaks, and the peak shape and peak position are consistent with those of commercial silicotungstic acid, proving the successful synthesis of silicotungstic acid.

[0028] from Figure 6It can be seen that the silicotungstic acid-based liquid flow battery system has stable charge and discharge performance with electron-by-electron (1~12e) cutoff. Therefore, the Keggin-configured silicotungstic acid prepared by a short process is an ideal candidate material for the multi-electron transfer electrolyte required for the design of a high energy density liquid flow battery system.

[0029] It can be seen that the Keggin configuration silicotungstic heteropoly acid-based flow battery negative electrode can achieve a maximum reversible redox of 12e, which is conducive to further constructing a high energy density flow battery system (relative to the 1e reversible redox of the all-vanadium flow battery).

[0030] Example 2 (1) Decomposition of scheelite and synthesis of silicotungstic heteropoly acid Weigh 50 g of calcium tungstate (CaWO 4(s) ) as the main component of scheelite powder and 10.44 g sodium silicate (Na 2 SiO 3 ) were added as precursors to the bottom of a three-necked flask, and an appropriate amount of 90 ℃ deionized water was added for soaking for 1.0 h; then, 5.0 mol / L hydrochloric acid was slowly added dropwise under strong stirring conditions, and the reaction was carried out for 2.5 h at a pH value of 4.5-5.5, a temperature of 100 ℃, and a solid-liquid ratio of 10. After the reaction was completed, the reaction mixture was filtered to separate the solid and the liquid, and the solution was retained. Keggin-structured silicotungstic heteropoly acid with a fixed ratio was obtained in the solution.

[0031] (2) Purification of battery-grade tungsten-silicon heteropoly acid electrolyte Add salt compounds with low solubility that can form compounds with silicotungstic heteropolyacid such as ammonium chloride, potassium chloride, sodium chloride, and tetrabutylammonium chloride to the filtered solution to form silicotungstic acid precipitate to achieve preliminary impurity removal of Keggin-configured silicotungstic heteropolyacid. The silicotungstic acid precipitate is dissolved in deionized water at 40 °C, and concentrated hydrochloric acid and ether are added and shaken well. The lowest layer of the mixed solution is transferred to another separatory funnel. After 2 times of hydrochloric acid acidification-ether extraction and purification, the oily solution at the lowest layer of the separatory funnel is evaporated by a rotary evaporator and dried to obtain silicotungstic heteropolyacid. To ensure purity, the obtained silicotungstic heteropolyacid is recrystallized 3 times to obtain silicotungstic heteropolyacid with battery-grade purity. In the process of re-dissolving the silicotungstic acid precipitate and acidification-ether extraction, the ratio of silicotungstic heteropolyacid weight: water volume: hydrochloric acid volume: ether volume usage basically meets 2:5:3:2. The obtained silicotungstic heteropoly acid has a battery-grade purity, in which the content of silicotungstic heteropoly acid is ≥99.5%, the impurity contents of Na, K, Ca, Fe, Zn and Cl are all less than 0.003%, and the leaching rate of scheelite is 99.70%.

[0032] Example 3 (1) Decomposition of scheelite and synthesis of silicotungstic heteropoly acid Weigh 50 g of calcium tungstate (CaWO 4(s) ) as the main component of scheelite powder and 6.96 g sodium silicate (Na 2 SiO 3 ) were added as precursors to the bottom of a three-necked flask, and an appropriate amount of 75 ℃ deionized water was added for soaking for 2.0 h; then, hydrochloric acid with a concentration of 3.0 mol / L was slowly added dropwise under strong stirring conditions, and the reaction was carried out for 5.0 h at a pH value of 4.5-5.5, a temperature of 75 ℃, and a solid-liquid ratio of 6. After the reaction was completed, the reaction mixture was filtered to separate the solid and liquid, and the solution was retained. Keggin-configured silicotungstic heteropoly acid with a fixed ratio was obtained in the solution.

[0033] (2) Purification of battery-grade tungsten-silicon heteropoly acid electrolyte Add salt compounds with low solubility that can form compounds with silicotungstic heteropolyacid such as ammonium chloride, potassium chloride, sodium chloride, and tetrabutylammonium chloride to the filtered solution to form silicotungstic acid precipitate to achieve preliminary impurity removal of Keggin configuration silicotungstic heteropolyacid. The silicotungstic acid precipitate is dissolved in deionized water at 40 °C, and concentrated hydrochloric acid and ether are added and shaken well. The lowest layer of the mixed solution is transferred to another separatory funnel. After 3 times of hydrochloric acid acidification-ether extraction and purification, the oily solution at the lowest layer of the separatory funnel is evaporated by a rotary evaporator and dried to obtain silicotungstic heteropolyacid. To ensure purity, the obtained silicotungstic heteropolyacid is recrystallized twice to obtain silicotungstic heteropolyacid with battery grade purity (wherein the content of silicotungstic heteropolyacid is ≥99.5%, the impurity content of Na, K, Ca, Fe, Zn, and Cl elements is not higher than 0.003%, and the leaching rate of scheelite is 99.62%). During the redissolution of the silicotungstate precipitate and the acidification-ether extraction process, the ratio of the weight of silicotungstic acid: the volume of water: the volume of hydrochloric acid: the volume of ether is basically 2:5:3:2.

[0034] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0035] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0036] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing heteropolyacids from scheelite in a short process, characterized in that: The steps include: S1. Scheelite and sodium silicate are soaked in water and acid-lyzed at a molar ratio of W to Si (1-3):1, so that the decomposed WO4 2- With SiO3 2- Under acidic conditions, it self-assembles into silicotungstic heteropoly acid with Keggin configuration, and then undergoes solid-liquid separation; S2, adding a precipitant to the leaching solution to make the silicotungstic heteropoly acid form silicotungstate precipitation, so as to achieve the preliminary purification of the Keggin-configured silicotungstic heteropoly acid; S3, re-dissolving the silicotungstate precipitate obtained in step S2, and obtaining silicotungstic heteropoly acid with battery grade purity through acidification, extraction and recrystallization.

2. The method according to claim 1, characterized in that In step S1, the tungsten element grade in the scheelite is greater than 40%, and the particle size is controlled at 0.038-0.074 mm.

3. The method according to claim 1, characterized in that In step S1, the water immersion conditions are: 75-90°C, solid-liquid ratio of 1g: (1-2 mL), 1.0-2.0 h.

4. The method according to claim 1, characterized in that In step S1, the acid hydrolysis conditions are: pH value 4.5-5.5, temperature 90-100°C, solid-liquid ratio of 1g: (3-10 mL), and time 2.5-5.0 h.

5. The method according to claim 1, characterized in that: In step S2, the precipitant is one or more of ammonium chloride, potassium chloride, sodium chloride, and tetrabutylammonium chloride.

6. The method according to claim 1, characterized in that In step S3, the redissolution temperature is 40-50°C.

7. The method according to claim 1, characterized in that In step S3, the acidification is carried out using hydrochloric acid, the extraction is carried out using ether, and the ratio of the weight of silicotungstic heteropoly acid, the volume of water, the volume of hydrochloric acid, and the volume of ether is 2:5:3:

2.

8. The method according to claim 7, characterized in that In step S3, the acidification-extraction times are 2 to 3 times, and the recrystallization times are more than 2 times.

9. Use of the heteropolyacid prepared by the method according to any one of claims 1 to 8 in preparing electrolyte for liquid flow batteries.

Citation Information

Patent Citations

  • Method for preparing silica tungsten heteropoly acid solution

    CN107032355A

  • Pre-treatment method for tungsten-containing minerals

    CN108642277A

  • High-calcium low-grade scheelite acid-alkali combined smelting process

    CN108998655A

  • Method for recovering tungsten from scheelite smelting slag

    CN111349788A

  • Method for leaching tungsten heteropoly acid through efficient acidolysis activation of scheelite

    CN114427039A

Cited By

  • Iron-substituted silicon-tungsten heteropolyacid salt electrolyte for high-capacity flow battery

    CN121149324A